Training on the Utilization of YouTube as an Interactive Learning Media for TKQ Al Falah Teachers - Khotijah, Siti; Driyani, Dewi; Haikal, Muhamad; J, Juliana (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The advancement of technology continues to grow, resulting in various forms of work requiring computers to support their activities. With computers, technology can be developed through internet networks, making it easier for people to obtain and disseminate information. The internet can also be used to develop learning processes. By utilizing the internet, teaching materials for students can be made more interesting, interactive, and varied. One of the internet technologies frequently used by kindergarten-age children is YouTube. YouTube is a social media platform that is highly popular among the public because it provides a wide range of educational, entertainment, and informational content. In the context of learning, YouTube can be utilized as a learning medium capable of increasing students’ interest and motivation in kindergarten education. Through engaging learning videos, students can more easily understand the material delivered by teachers. Therefore, training in the creation and use of YouTube as a learning medium for teachers at TKQ Al Falah is important to conduct. This activity aims to enable teachers to optimally utilize digital technology in the teaching and learning process, thereby creating learning experiences that are more innovative, creative, and enjoyable for children.